Katyn Dramas - Anatoly Dmitrievich Shutov (Проблемы постсоветского пространства, 2017)
This article addresses one of the most sensitive present-day issues in modern international relations - the Katyn tragedy. The unbiased outlook on this historical and international problem permits to restore the historical justice, to present objectively the picture of killing the Polish officers.